Ta’lim al-Lughaat al-Ajnabiyah wa al-Tarjamah Baina al-‘Aid al-Iqtishadi wa al-Tsaqafah al-Ma’rifiyah - Asmaa Mosa Othman (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The topic of teaching foreign languages and translation is one of the important topics for human existence as a whole. Language education and translation will be discussed from an economic point of view, as language is a tool for trading intangible assets and a tool of linguistic policy, while cash represents a tool for trading material assets and a tool of monetary policy. We find translation in exchange for currency conversion and foreign language in exchange for foreign exchange, where translating content from one language to another is similar to exchanging goods using money. I will discuss the relationship of language and translation to economics. Since languages are put into use by their communities, as important tools and means of communication, there are mutual relationships between language and the community. During this research, I will search for theoretical answers to important questions such as: 1- What is the relationship of language and translation to economics? 2- Can language be considered as a stock of money? 3- What is the importance of learning languages in developing creative thinking? 4- Is learning foreign languages an urgent economic need in the modern era? 5- Does translation affect the economy? Through these questions and their answers, comparisons will be made between the linguistic system and the economic system, and knowledge of the dynamics of expanding markets and language ranges, the emergence of unified and common European languages coinciding with the emergence of unified standard currencies and common markets and their impact on national markets, and how language itself became a commodity, directed to linguistic markets, with a regional and global dimension. Keywords: languages - economics - translation - creative thinking